PERSONALITY AND ADJUSTMENT TO A LOW-CONTROL SITUATION: THE MEDIATING ROLE OF COPING - Buško, Vesna (Array, 2001)
The hypothesized mediating effects of coping mechanisms in the stress and adjustment processes were tested in a prospective framework with 421 basic military trainees. Structural equation analyses indicated direct relations of personality assessed by NEO-FFI to the changes in psychological adjustment when the model included initial coping measures. Personality effects on adjustment were, however, fully mediated through the measures of later coping.